Prevalence of Cardiovascular Risk Factors among Community During Screening Campaign in Makkah 2022-2023 - Dr. Reham Naif Bin Hassan; Dr.Bashaier Ahmad Fairaq; Dr. Mansour Matok Madabighy; Fayza Humod Alhazmy; Dr. Yasmeen Ismael Barnawi; Dr.Bayan Saleh Bin saeed; Dr.Wael Hassan Alzahrani; Zainab Talha Hawsawi; Abdullah Saeed Alyamani; Kawther Habiballah Turkistani (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: This study aimed to set up a database of the prevalence of CVD risk factors and their relation to others for the population in the Makkah region, which helped empower the planning for future campaigns and screening programs. Material and Method: This cross-sectional study has been performed from January 2022 to August 2023. We measured the prevalence of overweight, obesity, diabetes, and hypertension in 4405 males and 1627 females in Makkah city.The data was collected using an Electronic Excel Sheet. All measurements were taken by trained staff and volunteers. Results: the prevalence of CHD risk factors among the study population according to measurement and laboratory results. About 41.6% obese, 36.8% overweight, and 19.2% normal. The body mass index for females [29.0±.60] was higher than that of males[p<0.05]. Also, the mean of random blood sager for females was higher than that for males [p<0.05]. However, the mean of SBP, and DBP were higher among males than females [p<0.05]. Conclusion: Our study confirmed a relationship between risk factors like obesity blood sugar levels and the development of coronary heart diseases. The lowest risks have been seen in people with lower body mass index and normal pressure.